Technological-Knowledge Bias and the Industrial Structure under Costly Investment and Complementarities. - Sochirca, Elena (2014)
We develop an extended directed technological change model with vertical and horizontal R&D to analyze the economic growth rate, the technological-knowledge bias and the industrial structure, assuming: (i) complementarities between inter- mediate goods, and (ii) internal costly investment. We nd that complementarities directly a ect long-run technological-knowledge bias and relative production, both elements in uence the economic growth rate and neither a ect the skill premium and the relative number of rms. We also verify that the relationship between the relative supply of skills and both economic growth and the industrial structure suggested by our model is qualitatively consistent with recent empirical data for a number of developed countries.